2019
DOI: 10.1007/s10833-019-09356-0
|View full text |Cite
|
Sign up to set email alerts
|

The English Teaching Excellence (and Student Outcomes) Framework: Intelligent accountability in higher education?

Abstract: This paper explores what underlies the recent introduction of a Higher Education Teaching Excellence Framework (TEF) in England. Related changes to the higher education landscape are discussed: the 2017 Higher Education Act and creation of a new HE regulator, the Office for Students. How TEF works and some of the consequences of TEF are outlined. As well as discussing what constitutes teaching excellence and what TEF itself is attempting to signal (which includes graduate destinations), we also analyse the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This study aims to provide recommendations for promoting excellence in teachinglearning processes [6,51]. Following the 2030 agenda for sustainable development goals [7], the design of this study focuses on students and how they learn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aims to provide recommendations for promoting excellence in teachinglearning processes [6,51]. Following the 2030 agenda for sustainable development goals [7], the design of this study focuses on students and how they learn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this research endeavors to go beyond the relationship between learning styles and performance by also evaluating the congruency between performance in different assessment methods and learning preferences. In line with the goal of achieving a university education based on excellence, tailored to the needs of students and ensuring equal opportunities [1,6], the purpose of this study is to identify the learning preferences of high-performing students, as well as to detect dimensions that may improve the results of lower-performing students in order to provide recommendations to teachers.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to TEF, teaching excellence was defined by the metrics that were used to measure teaching excellence. It is for the reason that Deem and Baird (2020) argued that the TEF is best understood as an index rather than a measurement where the different elements of the index (the TEF metrics) define the nature of teaching excellence. This is supported by Matthews and Kotzee (in press) who analysed the institutional statements and found that successful statements tended to be those that reflected the metrics by focusing on employment, employability and student outcomes.…”
Section: Tqef and Tef As Policy Instrumentsmentioning
confidence: 99%
“…Achieving teaching excellence in university education is one of the top priorities in current university teaching plans [1,2]. The definition of teaching excellence has been conceptualized from a variety of approaches.…”
Section: Introductionmentioning
confidence: 99%